PENGEMBANGAN E-LKPD DENGAN APLIKASI LIVEWORKSHEETS PADA ELEMEN PERHITUNGAN STATIKA BANGUNAN KELAS X DPIB DI SMK NEGERI 2 MEDAN - Sartika Aritonang, Rani; Sutrisno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the need for engaging and interactive learning media to support the learning process in the subject of Building Statics Calculation Elements. This research aims to determine the feasibility of the E-LKPD product with the liveworksheets application used in the Building Statics Calculation element. The research method used is Research and Development (R&D) with the ADDIE development model modified to ADD (Analysis, Design, Develop). The instrument used is a questionnaire. The questionnaire is used to test the feasibility of the E-LKPD through validation by material experts and media experts. The results of the study show that the developed E-LKPD product obtained an average value from material experts of 4.42 (category "very feasible"), and obtained an average value from media experts of 4.20 (category "very feasible"). Thus, the development of the E-LKPD with the liveworksheets application according to experts is very feasible for use by Grade X DPIB students at SMK Negeri 2 Medan, therefore it is recommended that future research proceed to the implementation and evaluation phases and assess the effectiveness of the media on students’ learning outcomes.